The Performance Design of Betel Nut Cutter in Rural Areas - Syawaldi, Syawaldi (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
Betel nut is one of leading agricultural commodity in Indonesia. The economic prospect of Betel Nut could support financially the people which resided in country-side to a new level of prosperity. The increasing of betel nut demand especially which derived from outside of country such as India and Thailand of the Betel Nut which is used as the raw material for medicine and cosmetic products will need new machine design of betel nut cutter to supply the demand. Current process of betel nut manufacture is still use a hand-tool for cutting the Betel Nut in rural areas. It takes lot of time and resulted low productivity. The design of the machine betel nut manufacture provides the solution to increase the productivity and low production cost because of cut in half process is still manually. This equipment can produce the cutting work with average 300 Betel Nut per hour. The force resulting from lever is 0.03 N and the cutting speed for 1 fruit only takes 4 seconds. This equipment is able to cut in half of two or three the Betel Nut in one time. This cutting machine prototype has been used widely in rural area of Riau province like village of Penyalai-Kuala Kampar, district of Pelalawan and several villages in the district of Indragiri Hilir.